A Scalable Cross-Chain Data Asset Rights Confirmation Framework for Distributed Systems Based on Hybrid Post-Quantum Zero-Knowledge Proofs - Zhang, Lila; Yan, Zhen (EAI Endorsed Transactions on Scalable Information Systems, 2026)
Abstract: In the era of the digital economy, establishing an efficient and compliant data asset rights confirmation system within scalable distributed infrastructures is of critical importance. However, under heterogeneous distributed ledger environments, data circulation is often trapped in a binary tension between privacy preservation and regulatory accessibility, while facing severe scalability bottlenecks. Existing studies lack a unified solution that simultaneously addresses cross-chain interoperability, post-quantum security, and low-cost verification. To this end, this paper proposes a data asset rights confirmation framework based on hybrid post-quantum zero-knowledge proofs. The framework designs a scalable recursive composition architecture combining Scalable Transparent Argument of Knowledge (STARKs) and Succinct Non-interactive Argument of Knowledge (SNARKs), leveraging off-chain compressed permutation to significantly reduce on-chain storage overhead. In parallel, a light-client-based distributed cross-chain state synchronization protocol and a regulation-friendly privacy auditing module (based on threshold encryption) are constructed to ensure transactional atomicity and conditional auditability during data circulation. Experimental evaluations conducted on two datasets, Ethereum NFT transactions and credit card fraud detection, demonstrate that, compared with cross-chain privacy-preserving solutions such as zkCross, the proposed framework reduces on-chain verification Gas costs by approximately 18.2%, compresses proof size to 0.28 kB, and achieves a peak throughput of 1,618 Transactions Per Second (TPS). Moreover, under controlled experimental conditions, the framework attains an audit success rate of 99.6% with only 14.0% performance overhead. Overall, this study alleviates the long-standing trade-offs among privacy protection, regulatory compliance, and computational scalability, and provides a verifiable technical solution for the interoperability and infrastructure development of next-generation distributed systems.
Keywords: data asset rights confirmation; zero-knowledge proofs; distributed systems; cross-chain interoperability; scalability